Fake news: relation between personality traits, social influence, and susceptibility to accept them as truth - De la Oliva Alzamora , María Paula (2023)
This research explores the possible influence of the big five personality factors and the susceptibility to social influence on the susceptibility to accept fake news (disinformation). The understanding of this phenomenon due to individual differences is a barely researched subject. Nevertheless, the massive spread of false information on social media and its consequences show the importance of this research. The research used a fake news task, adapted versions of the SPTS (Susceptibility to Persuasion Scale), and the Mini-IPIP (International Personality Item Pool) as measurement tools. Using multiple linear regression analysis, it also assessed two models to predict susceptibility to accept fake news. The results show that certain personality traits and susceptibility to social influence may be useful predictors of the dependent variable, particularly in the context of social influence in news consumption on social media. This article recommends corrections for the questionnaires and suggests some hypotheses regarding the interaction of personality, social influence, and susceptibility to accepting fake news for further research.